Primary care physicians’ attitudes and perceptions towards antibiotic resistance and outpatient antibiotic stewardship in the USA: a qualitative study - Jeffrey A Linder; Jason N Doctor; Rachel M Zetts; Andrea Stoesz; Andrea M Garcia; Jeffrey S Gerber; David Y Hyun (BMJ Open)
Objectives At least 30% of outpatient antibiotic prescriptions are unnecessary. Outpatient antibiotic stewardship is needed to improve prescribing and address the threat of antibiotic resistance. A better understanding of primary care physicians (PCPs) attitudes towards antibiotic prescribing and outpatient antibiotic stewardship is needed to identify barriers to stewardship implementation and help tailor stewardship strategies. The aim of this study was to assess PCPs current attitudes towards antibiotic resistance, inappropriate antibiotic prescribing and the feasibility of outpatient stewardship efforts.Design Eight focus groups with PCPs were conducted by an independent moderator using a moderator guide. Focus groups were audio recorded, transcribed and coded for major themes using deductive and inductive content analysis methods.Setting Focus groups were conducted in four US cities: Philadelphia, Birmingham, Chicago and Los Angeles.Participants Two focus groups were conducted in each city—one with family medicine and internal medicine physicians and one with paediatricians. A total of 26 family medicine/internal medicine physicians and 26 paediatricians participated.Results Participants acknowledged that resistance is an important public health issue, but not as important as other pressing problems (eg, obesity, opioids). Many considered resistance to be more of a hospital issue. While participants recognised inappropriate prescribing as a problem in outpatient settings, many felt that the key drivers were non-primary care settings (eg, urgent care clinics, retail clinics) and patient demand. Participants reacted positively to stewardship efforts aimed at educating patients and clinicians. They questioned the validity of antibiotic prescribing metrics. This scepticism was due to a number of factors, including the feasibility of capturing prescribing quality, a belief that physicians will ‘game the system’ to improve their measures, and dissatisfaction and distrust of quality measurement in general.Conclusions Stakeholders will need to consider physician attitudes and beliefs about antibiotic stewardship when implementing interventions aimed at improving prescribing.